Root-shoot ratio of maize (Zea mays L.) as influenced by different levels of water deficit under two different climatic conditions - Othman, Mardin; Mohammed, Aram Abbas (Sulaimani Journal for Pure and Applied Sciences, 2018)
In order to determine the effect of water stress on biomass accumulation of root and shoot, and their ratio of two maize hybrids (Zea mays L.) under the effect of three different irrigation levels, two different field experiments were conducted in a silty clay soil during the autumn season of 2014 and spring season of 2015 at the Agricultural research station of Qlyasan – University of Sulaimani. A split plot design with three replications were used. Three different levels of irrigation were applied, I1 represented the water requirements of the two hybrids along the growing season from seedling to physiological maturity, I2 breaking one irrigation after each two irrigation during the vegetative growing season only, but I3 applied with breaking one irrigation after each two irrigations during the vegetative and reproductive growing season till physiological maturity. Effect of water deficit levels on the growth and development of root and shoot as well as the root-shoot ratio were determined. The root-shoot ratio of the two hybrids was increased with the extended growing period through the growing seasons. The effect of I3 level of maize root- shoot ratio was greater in comparison to I1 and I2. There were differences in response of H1 and H2 to irrigation levels, the ratio of root to shoot for the H2 was greater than H1 in both seasons.
Keywords: Water deficit; irrigation levels; rootshoot ratio; root and shoot growth